Rythmanalyse et lire-écrire dans l’esthétique concrète de G. Bachelard : la miniature et la poétique de la lampe - Reda, Viviana (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2020)
The discovery of rêverie as a dimension of the aura of consciousness, and as an independent form of awareness of the world, leads the epistemologist, Gaston Bachelard, into the realm of aesthetics research. Imagination has a material and a dynamic nature, that enables us to move beyond the rigid framework of psychoanalytical interpretation. Rhythmanalysis, which Bachelard takes up where the Portuguese writer Pinheiro Dos Santos left off, reconciles, within the reality of the imaginary, the rhythm of aggression and distension, in line with the dual valorization of poetic images of the elements. Poetry, which embodies the passions of matter, animates the relationship between man and his world. This concrete aesthetic finds its fundamental rationale in the epistemological research of the philosopher Bar-sur-Aube, where it is refelected in the debate about time and space in poetry, in Miniature and in Immensity. The form of this concrete aesthetic is a written meditation that originates and dies with its reading, in a unified process of reading-writing, which can be embodied in the image of the Phoenix. Keywords: Concrete Aesthetic, Rhythmanalysis, Reading-Writing, Passions Of Matter, Miniature And Immensity.